DC–T cell virological synapses and the skin: novel perspectives in dermatology. Issue 1 (11th November 2014) - Shimauchi, Takatoshi; Piguet, Vincent
Abstract Virological synapses (VS) increase cell‐to‐cell viral transmission and facilitate propagation of human immunodeficiency virus type 1 (HIV‐1) and human T‐cell leukaemia virus type 1 (HTLV‐1). VS formation also plays a more general role in viral replication and dissemination. VS have been observed in vitro and ex vivo between uninfected T cells and T cells infected with HIV‐1 or HTLV‐1. In addition, dendritic cells (DC) infected with HIV‐1 also play an important role in viral transmission to uninfected CD4+ T cells via VS formation. Recent studies revealed that several DC subsets are also infected with HTLV‐1. These findings may help explain the rapid dissemination of both viruses within secondary lymphoid tissues in vivo. VS also explain, at least in part, why HIV‐1 can propagate in the mucosal sites during sexual transmission. Furthermore, in the case of HTLV‐1, VS can potentially explain some of the features of HTLV‐1‐associated dermatitis as infected T cells in the skin contribute to the pathogenesis of this condition.